De Novo sequencing and assembly of the pineapple genome and comparative transcriptomics of two development stages of the fruit - Raimi Mohamed Redwan (2017)
Pineapple (Ananas comosus var. comosus) is the third most important fruit globally after banana and citrus. Genetic information of the species will help expedite pineapple improvement program in producing elite cultivar and to facilitate understanding of its molecular mechanism. As such, this project aims to de novo sequence, assemble and annotate the genome of the commercially important MD-2 pineapple. The draft genome was then used as a reference to identify genetic variations in the Babagon pineapple (which is a domesticated local Sabah variety) and for comparative genomic study among the sequenced member of the sub-class Commelinidae. Furthermore, gene expression profiling of two developmental stages of the ripening fruit, specifically the mature green and mature yellow fruits, were performed using in-house available transcriptomic data. The genome was sequenced using two leading-edge sequencing technologies i.e. the highly accurate short Illumina reads and the ultra-long PacBio reads. A total of 110 Gbp reads were obtained which constitute 209X coverage of the pineapple genome. The final assembly of the MD-2 pineapple genome achieved an NS0 scaffold of 153,084. Approximately, 27,017 protein-coding genes were predicted with 45.21% of the genome were identified as repetitive elements. Analyses of the Babagon variety showed one variant in every 108 bases with 86.6% of the variants composed of single-nucleotide variant (SNVs) and the remaining were insertion or deletion. The Ka/Ks analysis revealed that 48 genes in the Babagon pineapple differ significantly in comparison to MD-2. Among them were genes that are involved in the synthesis of terpene and plant defence system. Transcriptome analysis at the fruiting stage of the Babagon pineapple revealed several key genes related to the production of 4-hydroxy- 2,5-dimethyl-3{2H)-furanone (HDMF), which is known to contribute to the flavour of pineapple. Furthermore, the genome-assisted-transcriptomic analysis suggests the important role ethylene plays in non-climacteric fruit, especially at the early stage of ripening and not throughout the ripening process as observed in climacteric fruit. The draft genome of the MD-2 pineapple has facilitated genomic analysis of pineapple as shown in the study and will allow further downstream applications that may have been hindered previously due to the lack of genomic information.